Analisis Korelasi Tanggap Darurat Bencana Terhadap Kesiapsiagaan Perawat - Abil Rudi; Kafi Pangki Suwito; Septina Boru Saragih (Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
Disaster response by nurses in border areas requires an effective strategy to improve disaster preparedness and response. The purpose of this study was to determine the relationship between disaster emergency response and nurse preparedness in border areas. The study design used an analytical survey with a cross-sectional technique. The number of respondents was 126 nurses in border areas with a purposive sampling approach and analysis using the chi-square test. The study showed that the majority of nurses' preparedness level was good (71.4%). Research variables that were significantly related to nurse preparedness included nurse response with a Pvalue = 0.030, emergency response time with a Pvalue = 0.016 and emergency/disaster training with a Pvalue = 0.042. It is recommended that nurses in border areas need to increase the frequency and quality of disaster emergency training periodically to strengthen nurse preparedness and can optimize response time quickly and accurately.